1995
DOI: 10.1111/j.1559-1816.1995.tb00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Managerial Disclosure of AIDS Health Information to Coworkers

Abstract: This research investigates the importance of legal concerns over lawsuits, fear of AIDS in the workplace, and gender as factors influencing a manager's decision to disclose AIDS health information to coworkers. Data was obtained from questionnaires administered to managers employed in service, manufacturing, and government organizations. Findings indicate that both fear of AIDS in the workplace and concern over lawsuits exhibited a significant relationship with the likelihood of sharing AIDS health information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…nearly three quarters of major U.S. companies responding to a survey administered by the American Management Association (2000) said that they record and review employees' telephone calls, e-mail messages, and Internet activities. Growth in testing areas of personality, honesty, and drug use, and the ease with which personal background information can be obtained by organizations, also appear to potentially threaten workers'privacy (Bylinsky, 1991;Culnan, 1993;Smith, 1993;Vest, Vest, Perry, & O'Brien, 1995). These practices increasingly affect a wide variety of workers, including professionals and managers.…”
mentioning
confidence: 99%
“…nearly three quarters of major U.S. companies responding to a survey administered by the American Management Association (2000) said that they record and review employees' telephone calls, e-mail messages, and Internet activities. Growth in testing areas of personality, honesty, and drug use, and the ease with which personal background information can be obtained by organizations, also appear to potentially threaten workers'privacy (Bylinsky, 1991;Culnan, 1993;Smith, 1993;Vest, Vest, Perry, & O'Brien, 1995). These practices increasingly affect a wide variety of workers, including professionals and managers.…”
mentioning
confidence: 99%
“…The patient's information should be disseminated on a need-to-know basis only. 23 Codes of ethics for healthcare professionals have some form of confidentiality as a requirement. It was suggested that with regard to maintaining patient confidentiality during teaching and case studies, the presentation should be conducted in a seminar room, rather than at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies investigating the relationship of AIDS fear and attitudes toward organizational privacy have yielded similar results. For example, in their study of a group of public administrators, Vest et al (1995) found that those who expressed greater fear of AIDS also reported that AIDS health records should be disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study draws attention to the potential dilemmas organizations may experience as AIDS takes its toll on Singapore. Managers may find themselves having to precariously balance conflicting interests, namely, the organization's and its employees' rights to gain access to AIDS health records as opposed to the PWHIV's right to privacy (Greene, Parrott, & Serovich, 1993; Vest, Vest, Perry, & O'Brien, 1995). It is hoped that organizations will become more aware of their responsibilities toward their employees' sense of well-being at work.…”
mentioning
confidence: 99%